Analisis Pendayagunaan Wakaf Uang Untuk Investasi Saham Syariah Sebagai Alternatif Wakaf Produktif - Putra, Humam Dzaki; Musfiq A, M Ridho; Ramadhan, Muhammad Faris (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, Semarang, 2021)
Indonesia is a large country with 270 million people living in the country. By that total population, Indonesia places 4th largest population in the world. Waqf is one important maliyah worship and has enermous conomic potential. Dr. Oni Sahroni (DSN-MUI Member) explained that sharia stock, if reviewed in the science of jurispridence, is permissible in Islam. However, it should also be noted that every investment always has a risk. Therefore, in this study the author will try to fully review how to utilise cash waqf in the form of sharia stock. This research uses a descriptive study method by examining various information on waqf management from various secondary sources (previous research) to produce a result and conclution of this study related to waqf management issues. In general, the model for implementing stock-based waqf is derived from profit of stock management which are then given to the waqf management institution to then be converted into waqf benefits in the form of productive assets and physical assets for society benefit. In more detail, there are two models of implementing stock waqf in Indonesia and the potency of stock waqf in this country is very large.